2018
DOI: 10.1002/ep.12974
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic iron‐manganese oxide coated graphene oxide and its application for adsorptive removal of basic dyes from aqueous solution: Isotherm, kinetics, and thermodynamic studies

Abstract: Adsorptive removal of cationic dyes such as methyl violet (MV) and methyl green (MG) from aqueous solution using magnetic iron‐manganese oxide coated graphene oxide (IMGO) was examined. The IMGO was characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive X‐ray spectroscopy, X‐ray diffraction (XRD), N2 adsorption–desorption isotherm, and vibrating sample magnetometer. The effect of different process parameters such as contact time, IMGO dose, initial dyes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…It is also worth noticing that the mGO did not have any toxicity effect on seeds, suggesting that the nanomaterial is safe for application in water and wastewater treatment. Unlike what occurs with pristine graphene oxide in water, which, even at low concentrations, can cause phytotoxicity in cabbage, tomatoes, red spinach, and lettuce [37]. As in this study, Fraga et al [26] did not observe inhibitory effects when using an iron-based GO adsorbent in the treatment of textile effluents, as the seeds of Lactuca sativa L. presented a growth of 95% of the seeds at different dilutions.…”
Section: Phytotoxicity Testssupporting
confidence: 39%
“…It is also worth noticing that the mGO did not have any toxicity effect on seeds, suggesting that the nanomaterial is safe for application in water and wastewater treatment. Unlike what occurs with pristine graphene oxide in water, which, even at low concentrations, can cause phytotoxicity in cabbage, tomatoes, red spinach, and lettuce [37]. As in this study, Fraga et al [26] did not observe inhibitory effects when using an iron-based GO adsorbent in the treatment of textile effluents, as the seeds of Lactuca sativa L. presented a growth of 95% of the seeds at different dilutions.…”
Section: Phytotoxicity Testssupporting
confidence: 39%
“…[13] In recent years, graphene/ manganese dioxide composite electrode materials have be-come a hot point for seeking superior supercapacitive performance. [14][15][16][17] Graphene, a hexagonal honeycomb lattice composed of sp 2 hybrid carbon atoms, [18] is a new but very competitive candidate for electroactive carbon electrode material, [19] due to its excellent electrical conductivity, [20,21] mechanical strength [22] and specific surface area. [23] So far, the fruitful scientific research results have confirmed its potential application as electrode materials in solar cells, [24] secondary batteries, [25] and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to avoid the shortcomings of single kind of material, it is feasible to develop high‐performance composite electrode materials by using the synergistic effect of electrode materials based on different energy storage mechanisms [13] . In recent years, graphene/manganese dioxide composite electrode materials have become a hot point for seeking superior supercapacitive performance [14–17] …”
Section: Introductionmentioning
confidence: 99%
“…produce colored effluents, which require a prior treatment before their discharge into water sources 2 . The presence of dyes in water bodies can generate problems such as the reduction of the photosynthetic activity of the aquatic flora due to the dyes obstructing the passage of solar light through the water 3,4 . In humans, dyes can cause damage to the central nervous system, reproductive system, and kidney dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…2 The presence of dyes in water bodies can generate problems such as the reduction of the photosynthetic activity of the aquatic flora due to the dyes obstructing the passage of solar light through the water. 3,4 In humans, dyes can cause damage to the central nervous system, reproductive system, and kidney dysfunction. Many dyes are toxic and, in some cases, can be carcinogenic, being made of aromatic compounds such as benzidine.…”
Section: Introductionmentioning
confidence: 99%